Taxonomic and habitat update to Phyllanthus narayanswamii (Phyllanthaceae): an endemic and endangered species from southern India - Satish, Koppineedi V.; Rao, Jonnakuti P. (Phytotaxa, 2019)
The present paper provides the supplementary information to Phyllanthus narayanswamii, which includes a detailed morphology, population, species associations, conservation status, current distribution, vegetation and land cover across different habitats and threats to the species survival in the habitats of uniqueness.